Time-dependent reliability analysis for repairable consecutive-k-out-of-n:F system - Gokdere, Gokhan; Ng, Hon Keung Tony (Taylor & Francis Ltd, 2022)
In a repairable consecutive C ( k , n : F ) system, after the system operates for a certain time, some components may fail, some failed components may be repaired and the state of the system may change. The models developed in the existing literature usually assume that the state of the system varies over time depending on the values of n and k and the state of the system is known. Since the system reliability will vary over time, it is of great interest to analyse the time-dependent system reliability. In this paper, we develop a novel and simple method that utilizes the eigenvalues of the transition rate matrix of the system for the computation of time-dependent system reliability when the system state is known. In addition, the transition performance probabilities of the system from a known state to the possible states are also analysed. Computational results are presented to illustrate the applicability and accuracy of the proposed method.
Keywords: Repairable consecutive-k-out-of-n; F system; transition rate matrix; time-dependent reliability; time-dependent transition performance probability